MORPHOLOGICAL CHARACTERISTICS OF BOSNIAN ARABIAN HORSE (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Horse breeding in our country is represented by private breeders, equestrian clubs. Thanks to them, the breeding of horses of the Arabian breed continued. The paper measures and presents the results of ten body measurements of 58 heads (21 stallions and 37 mares), Arabian breeds. The number of measured heads of individual lines and genera is as follows: Lenkoran 5; Gazal 5; Saabich 6; Siglavy 4; Kuhaylan Zaid 1, Kublay 1, Kadina 13; El Hafi 6; Luna 6; Hamdani 7; O’Bayan 3; Saklawi 1; Kuhaylan 1.The average height of the ridge was found to be 147.00 ± 0.39 cm, the length of thehull 144.5 ± 0.52 cm. If we observe the relationship between the height of the ridge and the length of the body, we see that the Bosnian Arabian horse is more square in shape and that its height at the withers is on average 3 cm higher than its body length. This shows us that this is a compact, solid horse whose back is shorter and able to withstand a heavier load.